ANALYSIS AND DESIGN FTTH (FIBER TO THE HOME) NETWORK WITH GPON TECHNOLOGY AT PT TELKOM, Tbk - Noyan Bathara P Siahaan; Solly Aryza; Siti Anisah (INFOKUM, 2022)
In today's era, the need for telecommunication, information and entertainment facilities that can be accepted and have high performance is definitely very much needed. To fulfill this, a network that supports its performance is needed. For now the network that is able to provide the best performance is optical fiber. In Indonesia itself, there is a rise in the deployment of fiber optic cables directly to the house or called FTTH. The city of Medan is one of the cities that is densely populated, especially for the North Sumatra area. With these conditions, the FTTH network design is suitable to be implemented in this location. In the design, a survey using GPS will be developed into Google Earth and AutoCad data. In the design data can be estimated about the number of devices, specifications and position of the placement of the device from the STO to the position of the customer. This data is to be developed along with calculation data based on FTTH GPON. In the design of the FTTH GPON network, the direct measurement results obtained the Power Link Budget value of -18.283 dBm for the downlink (-8.248) ns for the uplink at the farthest point, and the Rise Time Budget, which was measured at the farthest point. The Rise Time Budget is <70% with a value of (0.363) nm for Downlink and (0.251) ns for Uplink.